2021
DOI: 10.3390/ijerph18073408
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Services Utilization and Health-Related Quality of Life of Syrian Refugees with Post-Traumatic Stress Symptoms in Germany (the Sanadak Trial)

Abstract: Refugees who have fled from the ongoing civil war in Syria that arrived in Germany often develop post-traumatic stress symptoms (PTSS). The aim of this study was to determine health care services utilization (HCSU), health care costs and health-related quality of life (HrQoL) of Syrian refugees with mild to moderate PTSS without current treatment in Germany. The study was based on the baseline sample of a randomized controlled trial of a self-help app for Syrian refugees with PTSS (n = 133). HCSU and HrQoL bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Approximately half of the refugees were under 40 years of age compared to 9% in the Swedish sample, and there exists a known and very strong negative association between age and HRQoL. The estimated mean index score is also somewhat higher than the 0.82 value found in a study of Syrian refugees resettled in Germany [ 18 ]. Possible explanations for this difference include the use of value sets obtained from different populations (Sweden versus Germany).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Approximately half of the refugees were under 40 years of age compared to 9% in the Swedish sample, and there exists a known and very strong negative association between age and HRQoL. The estimated mean index score is also somewhat higher than the 0.82 value found in a study of Syrian refugees resettled in Germany [ 18 ]. Possible explanations for this difference include the use of value sets obtained from different populations (Sweden versus Germany).…”
Section: Discussionmentioning
confidence: 87%
“…Few studies in the published literature to date have explored HRQoL in refugee populations using such a preference-based approach. One study of 133 Syrian refugees in Germany found that the HRQoL of the refugees reported was lower compared to a representative German population sample [ 18 ]. A prior publication by our research group used the EQ–5D–5L index score to examine gender differences in HRQoL in Syrian adult refugees resettled in Sweden but based on the United Kingdom population data as no value set was available for the Swedish population at the time [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…They were also equal to the annual resource use costs for Syrian refugees of €1920 reported by a RCT using a bottomup approach. 37 The main cost driver in all studies was in-patient healthcare, owing to inadequate provision of or access to primary and preventive care. 14 In addition, Empowerment proved to be effective in reducing depressive symptoms in RAS.…”
Section: Discussionmentioning
confidence: 99%
“…This scale has been shown to be reliable with α=0.88 8 . Domains of the EQ-5D include anxiety/depression, usual activities (e. g., housework, study, work, leisure, or family activities), mobility, self-care, and pain/discomfort 23 .…”
Section: Methodsmentioning
confidence: 99%
“…3) The QoL was evaluated using the quality-of-life questionnaire entitled EQ-5D [23]. The EQ5D (five-level version) contained five items with each having five response options: 1 (no problems), 2 (slight problems), 3 (moderate problems), 4 (severe problems), and 5 (extreme problems).…”
Section: Research Instrumentsmentioning
confidence: 99%